2014
DOI: 10.1155/2014/781675
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Comprehensive Health Care Program by Korean Medicine Doctors on Medical Care Utilization for Common Infectious Diseases in Child‐Care Centers

Abstract: As the role of traditional medicine in community health improvement increases, a comprehensive health care program for infectious diseases management in child-care centers by Korean medicine doctors was developed. The purpose of this study is to evaluate the effects of the program intervention on infection-related medical care utilization among children. The study used a quasi-experimental design with nonequivalent control group, comparing pre- and post-intervention data of the same children. The program imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…The program significantly reduced the number of outpatient visits both in the main analysis, and in the sensitivity analysis. This is consistent with that reported in a study by Park et al [ 28 ], which evaluated a TKM-based healthcare program for preventing infectious diseases in infants. This may suggest that providing TKM doctor visits to CCCs and herbal medication could reduce the number of outpatient visits.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The program significantly reduced the number of outpatient visits both in the main analysis, and in the sensitivity analysis. This is consistent with that reported in a study by Park et al [ 28 ], which evaluated a TKM-based healthcare program for preventing infectious diseases in infants. This may suggest that providing TKM doctor visits to CCCs and herbal medication could reduce the number of outpatient visits.…”
Section: Discussionsupporting
confidence: 93%
“…“Please mark an X on the below scale to indicate how your child’s health is TODAY.”) were only included in the calculation. These periods were set considering their consistency with Park et al [ 28 ]. The EQ-5D index was calculated using the method proposed by the Korea Centers for Disease Control and Prevention [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…The signi cant decrease in the number of outpatient visits is consistent with that reported in the study by Park et al [23], which was conducted to evaluate a TKM-based healthcare program for preventing infectious diseases in infants. This result showed that providing TKM doctor's visits to CCCs and necessary herbal medication over-the counter had the effect of replacing outpatient visits of disadvantaged children.…”
Section: Discussionsupporting
confidence: 88%
“…Frequency measurements were limited to respiratory, digestive, ophthalmological, otolaryngological, and dermatological diseases, which have a large degree of incidence and clinical signi cance in children [20][21][22]. The number of outpatient visits, absence, and lateness/early leaves was limited to cases within the last 1 month, and the number of infectious symptoms was limited to cases within the last 2 weeks [23].…”
Section: Variablementioning
confidence: 99%
“…Jeong et al 27 reported that children with neuropsychiatric diseases who have other health problems use CAM more often than children who do not have other health problems. In addition, TKM has been used to improve physical strength, and children with disabilities in South Korea often have physical weakness, 28 nocturnal enuresis, 29 and emotional and behavioral disorders 30 as well as high rates of common infectious diseases 31 …”
Section: Discussionmentioning
confidence: 99%